Synthesis and fluorescence emission properties of D-π-D monomers based on dithieno[3,2-b:2′,3′-d]thiophene - Wang, Chuan-Zeng; Do, Jung-Hee; Akther, Tahmina; Feng, Xing; Matsumoto, Taisuke; Tanaka, Junji; Redshaw, Carl; Yamato, Takehiko (Journal of luminescence, 2017)
We herein present four highly fluorescent and stable D-π-D monomers (2), which were designed and synthesized using different types of aryl substituent as the donor via a Suzuki-Miyaura coupling reaction. We have studied these four symmetrical chromophores by UV–vis absorption and fluorescence emission spectroscopy both in solution and the solid state. This research shows that the introduction of the aryl groups can effectively reduced the HOMO-LUMO gap of thiophene chromophore resulting in a shift of the wavelength of the absorption and fluorescence emission. The notable optical features of their solid-state powders also exhibited a distinct red-shift in comparison with the emissions of their dilute solutions. These results combined with the theoretical calculations (B3LYP/6–31G*) indicate that these systems are promising candidates in the fabrication of organic electroluminescence devices.
Keywords: Biophysics; Atomic and Molecular Physics; and Optics; Biochemistry; General Chemistry; Condensed Matter Physics